Effect of Shampakadi Niruha Basti along with Patra Pinda Swedan in the Management of Gridharsi w.s.r to Sciatica (International Journal of Ayurveda and Pharma Research, 2024)
Gridhrasi is a common musculoskeletal disorder with radiating pain, stiffness, numbness and tingling sensation in one or both legs. Due to similar clinical presentation, Gridhrasi can be equated with Sciatica, in which there is pain in one or both legs caused by compression of the sciatic nerve or its component nerve roots (L5-S1). It generally affects the people in the productive years of their life and makes walking and standing painful, embarrassing and also limits their mobility. Conservative treatment options for Sciatica only provide momentary relief from pain with a very high recurrence rate. In the present report we discuss the case of a 70 years old female patient who presented with the complaint of severe low backache and pain radiation towards both legs up to the feet with associated numbness in the right leg. She was treated with Shampakadi Niruha Basti along with Patra Pinda Swedan for the time period of 16 days. There was significant improvement in the signs and symptoms of Gridhrasi i.e., SLR Test, pain, numbness, etc. Not only did the combination of these two treatment modalities alleviate the patient's symptoms but it also checked the recurrence of pain by relaxing and strengthening the musculature of the back.